The world heritage convention in a globalized world - Martorell Carreño, Alberto (2017)
The concept «world heritage» arises after the approval of the World Heritage Convention of UNESCO in1972. This document is focused in promoting the international responsibility towards the right conservation of cultural heritage goods that joint a special interest for the human community as a whole. Considering that heritage is a source for local and national identities, to understand the relationship between local and universal values is an issue that convokes the attention of the specialists. It is coherent to discuss on this relationships in the context of globalization Is it there a real process of creation of a «world heritage? Is it possible to sustain that the World Heritage List is the «global heritage list»? Do the goods inscribed (or, at least, the values represented by them) on the list represent to the human community? Which is the situation, among universal and local values, of the Peruvian sites inscribed on the universal list?